2019
DOI: 10.1002/lary.28336
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Effects on FOXP3+ and CD8+ T Cell Infiltrates of Head and Neck Squamous Cell Carcinoma

Abstract: ObjectivesAlterations of cellular metabolism have been implicated in immune dysfunction in the tumor microenvironment (TME) of head and neck squamous cell carcinoma (HNSCC). Metformin has recently emerged as a candidate of interest for combination with immunotherapy in HNSCC. This study investigated the effect of metformin on immune cell infiltrates of HNSCC.MethodsRetrospective analysis of T cell infiltrates in primary tumor specimens from patients enrolled in a clinical window of opportunity trial of presurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
2
23
0
1
Order By: Relevance
“…Eikawa et al demonstrated that metformin increases the number of CD8(+) TILs and enhances the efficacy of T‐cell‐mediated tumor cell lysis in a murine model 17 . Recent studies have shown that the number of CD8(+) TILs in human head and neck squamous cell carcinoma tumors (HNSCC) 33 and non‐small‐cell lung cell tumors 34 are increased in metformin‐treated patients, and is consistent with these results.…”
Section: Discussionmentioning
confidence: 59%
“…Eikawa et al demonstrated that metformin increases the number of CD8(+) TILs and enhances the efficacy of T‐cell‐mediated tumor cell lysis in a murine model 17 . Recent studies have shown that the number of CD8(+) TILs in human head and neck squamous cell carcinoma tumors (HNSCC) 33 and non‐small‐cell lung cell tumors 34 are increased in metformin‐treated patients, and is consistent with these results.…”
Section: Discussionmentioning
confidence: 59%
“…Another potential mechanism is the effect of metformin on Tregs, as it also inhibits mammalian target of rapamycin (mTOR). Metformin treatment for a minimum of 9 days before surgery of HNSCC, more than half being OPSCC, resulted in a strong decrease of intratumoral Foxp3+ Tregs and increase of stromal CD8+ T cells between pre-and post-treatment samples (n=16 HPV+ and n=20 HPV-negative), independent of HPV status (139). Potentially, metformin treatment may be interesting for HPV+ OPSCC patients with ongoing tumor immunity.…”
Section: Immune Modulatorsmentioning
confidence: 98%
“…The images were evaluated using digital analysis software (Visiopharm; Hoersholm, Denmark), which has been used previously for identifying T cells in the HNSCC TIME. 17 Red-Blue-Green color filters were set which reliably distinguished 3,3’-diaminobenzidine (DAB) stained and hematoxylin stained cells without detecting unstained negative space. Areas of artifact or damage were manually excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The images were evaluated using digital analysis software (Visiopharm; Hoersholm, Denmark), which has been used previously for identifying T cells in the HNSCC TIME. 17 Red-Blue-Green color filters were set which reliably distinguished 3,…”
Section: Ihcmentioning
confidence: 99%